A rearranged homoploid hybrid species of Origanum (Lamiaceae): O. ×munzurense Kit Tan & Sorger. Issue 2 (3rd April 2019) - Dirmenci, Tuncay; Özcan, Taner; Açar, Mikail; Arabacı, Turan; Yazıcı, Türker; Martin, Esra
ABSTRACT: Origanum munzurense Kit Tan & Sorger (Sect. Brevifilamentum Ietsw.) was described by Kit Tan & Sorger in 1984, and it is an accepted species related to O. acutidens (Hand.-Mazz.) Ietsw. belonging to sect. Brevifilamentum . It is morphologically intermediate between O. acutidens and O. vulgare L. subsp. gracile (K.Koch) Ietsw., and its type locality lies in the overlap zone between the geographic distributions of these two taxa. We hypothesized that O. munzurense is in fact a hybrid between the two aforementioned taxa and we tested this hypothesis with the general morphology, chromosome features, and nuclear (ITS1–ITS2) and chloroplast ( rpl 32) DNA sequences of specimens of O. munzurense and its putative parental species, O. vulgare subsp. gracile and O. acutidens . The somatic chromosome number of O. munzurense, O. vulgare subsp. gracile and O. acutidens were counted as 2n = 30. Origanum munzurense presented polymorphic sites in the nuclear ITS region, but the chloroplast markers did not allow us to identify the putative maternal of O. munzurense . Our results suggest that O. munzurense is indeed a hybrid, and its rearrangement as a new homoploid hybrid ( O . × munzurense ) would be more accurate. These present results support previous reports for the speciation of Origanum members via hybridization.